Interaction patterns of systemic problems in distributed energy technology diffusion: a case study of photovoltaics in the Western Cape province of South Africa. Issue 12 (2nd December 2018) - Kriechbaum, Michael; Brent, Alan C.; Posch, Alfred
ABSTRACT: Compared to large-scale renewable energy systems, distributed systems have diffused relatively slowly in recent years, particularly in developing countries. In this study, we analysed the barriers to the diffusion of distributed photovoltaics in South Africa by applying the technological innovation system framework. More specifically, we carried out an interview-based structural-functional analysis to identify underlying systemic problems, reveal their patterns of interaction, and analyse the implications of these patterns for the relationship among the key processes within the innovation system, the so-called system functions. We identified a variety of interlinked problems, shed light on the specific roles of different, mal-performing, system functions, and revealed constellations where specific functions blocked each other and, thereby, created lock-in situations. Although the findings reveal the complexity of the problems that are associated with the implementation of distributed energy technologies, they also indicate that these problems may be addressed successfully.